Seeds of good anthropocenes: developing sustainability scenarios for Northern Europe - Raudsepp-Hearne, Ciara; Peterson, Garry D; Bennett, Elena M.; Biggs, Reinette; Norström, Albert V.; Pereira, Laura; Vervoort, Joost M.; Iwaniec, David M; McPhearson, Timon; Olsson, Philip; Hichert, Tanja; Falardeau, Marianne; et al. (Springer, 2020)
Scenario development helps people think about a broad variety of possible futures; however, the global environmental change community has thus far developed few positive scenarios for the future of the planet and humanity. Those that have been developed tend to focus on the role of a few common, large-scale external drivers, such as technology or environmental policy, even though pathways of positive change are often driven by surprising or bottom-up initiatives that most scenarios assume are unchanging. We describe an approach, pioneered in Southern Africa and tested here in a new context in Northern Europe, to developing scenarios using existing bottom-up transformative initiatives to examine plausible transitions towards positive, sustainable futures. By starting from existing, but marginal initiatives, as well as current trends, we were able to identify system characteristics that may play a key role in sustainability transitions (e.g., gender issues, inequity, governance, behavioral change) that are currently under-explored in global environmental scenarios. We suggest that this approach could be applied in other places to experiment further with the methodology and its potential applications, and to explore what transitions to desirables futures might be like in different places.